CLASSIFICATION AND SELECTION CRITERIA SOFTWARE FOR FUNDAMENTALIZATION BACHELOR INFORMATYCHNYH COMPUTER SCIENCE DISCIPLINES - Kogut У.П. (Journal of Information Technologies in Education (ITE), 2012)
The article analyzes the different ways fundamentalization informative education, the criteria of choice of software tools which can be used for bachelors computer science. Analyzed the concept of computer mathematics and conditions of effective use of data systems in education bachelors science in the study informatychnyh disciplines.